Collaborative programming by demonstration in a virtual environment - Sung, Yunsick; Cho, Kyungeun (IEEE intelligent systems, 2012)
Collaborative learning for a robot, a software agent, and a human subject in a virtual environment reduces time, labor, and cost compared to real-life approaches.